Play to Learn? An Experiment - Dufwenberg, Martin (2009)
Does playing a game in class improve students' ability to analyze the game using game theory? We report results from an experimental design which allows us to test a series of related hypotheses. We fail to find support for the conjectured learning-enhancing effects and discuss what lessons can be learned substantially and methodologically